パーライト鋼線の限界拡散性水素量と吸蔵水素量に及ぼす伸線加工ひずみと時効温度の影響 - 小坂, 誠; 千田, 徹志; 久保田, 学; 樽井, 敏三; 大村, 朋彦 (鉄と鋼, 2019)
It is well-known that pearlitic steel wires have a higher resistance to hydrogen embrittlement than tempered martensitic steels. It is significant to clarify the effect of various mechanisms of the hardening on hydrogen embrittlement for the compatibility between high strength and resistance to hydrogen embrittlement. In this study, effects of drawing strain and aging temperature in pearlitic steel wires on hydrogen embrittlement properties were investigated. Absorbed hydrogen content after cyclic corrosion test (HE) was increased with added drawn strain and saturated with large amounts of drawn strain. Furthermore, the higher the aging temperature, the smaller HE is obtained. The critical diffusible hydrogen content (HC) in pearlitic steel wires aged at 450°C is higher than that aged at 250°C and as-drawn pearlitic steel wires. The reasons are considered to be a decrease in the dislocation density and suppression of crack propagation due to the short length of ferrite-cementite interface. Consequently, the pearlitic steel wires aged at 450°C are excellent in resistance to hydrogen embrittlement because HC is much higher than HE, although the tensile strength of pearlitic steel wires is decreased by aging at 450°C and above.